Tannins Can Have Direct Interactions with Anthelmintics: Investigations by Isothermal Titration Calorimetry - Sillanpää Mimosa; Engström Marica T.; Tähtinen Petri; Green Rebecca J.; Käpylä Jarmo; Näreaho Anu; Karonen Maarit (MDPI, 2025)
Plant tannins are known for their anthelmintic and antiparasitic activities and have been increasingly studied to battle the ever-growing problem of anthelmintic resistance. While tannins have been shown to exhibit these activities on their own, one approach would be to use them as complementary nutrients alongside commercial anthelmintics. So far, research on the interactions between tannins and anthelmintics is limited, and few studies have reported both synergistic and antagonistic effects depending on the type of tannin and the method used. These interactions could either strengthen or weaken the efficacy of commercial anthelmintics, especially if tannin-rich diets are combined with anthelmintics used as oral drenches. To study these interactions, a series of hydrolysable tannins (HTs) was selected, and their direct interactions with thiabendazole (TBZ) were evaluated by isothermal titration calorimetry (ITC), which allowed the detection of the exothermic interaction but also the roles and significances of different structural features of HTs in these interactions. Our results show that HTs can have a direct interaction with the benzimidazole anthelmintic TBZ and that the interaction is strengthened by increasing the number of free galloyl groups and the overall molecular flexibility of HTs.